Upaya Humas Kementerian Agama Sumsel dalam Mengelola Komunikasi dan Kerja Sama dengan Lembaga Pendidikan - Rosi Ayu Hermawanti; Eraskaita Ginting; Gita Astrid (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to describe and analyze the efforts of the Public Relations Office of the Regional Office of the Ministry of Religious Affairs of South Sumatra Province in managing communication and building cooperation with educational institutions. The focus of the study is directed at the communication patterns applied, relationship management strategies, as well as the obstacles and solutions developed by the Public Relations Office. The approach used is descriptive qualitative with in-depth interview, observation, and documentation techniques. The research results show that the Public Relations department has made efforts to carry out communicative and coordinative functions through the use of digital communication media, face-to-face meetings, activity publications, and routine evaluations with educational partners. The established cooperation is based on mutual trust, openness, commitment, and shared benefits. However, there are still challenges such as schedule changes, limited signal in some areas, and a shortage of PR human resources. Efforts to overcome these issues are made through rescheduling, strengthening communication, enhancing the use of digital media, and conducting cross-sector coordination.